Implementasi Teknologi Hybrid Internet of Things dan Logger dalam Pemantauan Tinggi Muka Air sebagai Sistem Peringatan Dini Kekeringan Lahan Gambut di Kelurahan Tahai, Palangka Raya, Kalimantan Tengah: Implementation of Hybrid Internet of Things and Logger Technology for Water Table Monitoring as an Early Warning System for Peatland Drought in Tahai Village, Palangka Raya, Central Kalimantan - Cassiophea, Lola; Anggraeni, Maya Erliza; Handayani, Noviyanthy; Genesa, Frans Putra; Kristianto, Nathanael Yanuar; Syahputra, Gagas Wira; Yustiana, Ana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Peatlands in Tahai Village, Palangka Raya, Central Kalimantan, play a crucial role as carbon sinks and water regulators, yet they are highly vulnerable to droughts that can trigger fires. Local communities have lacked access to an adequate early warning system, making it challenging to conduct timely mitigation. This community service program aims to implement a hybrid Internet of Things and logger technology to monitor water table levels in real-time, serving as an early warning system for drought. The devices consist of a water table sensor, air temperature and humidity sensors, and a soil moisture sensor, all connected to a microcontroller, cellular communication module, solar panel, and battery, serving as a stand-alone power supply. The program was carried out through socialization, training, device installation, field testing, mentoring, and evaluation. The results indicated a 68% improvement in community knowledge based on pre-test and post-test assessments. Three units of the system were successfully installed and operated continuously, recording data every 2 hours and delivering early warning notifications through text messages. This program has proven effective in increasing community preparedness, providing appropriate technology for environmental monitoring, and strengthening the role of local cadres in ensuring program sustainability.